Completion of Eight Gynostemma BL. (Cucurbitaceae) Chloroplast Genomes: Characterization, Comparative Analysis, and Phylogenetic Relationships - Zhang, Xiao; Zhou, Tao; Kanwal, Nazish; Zhao, Yuemei; Bai, Guoqing; Zhao, Guifang (Frontiers in Plant Science, 2017)
Gynostemma BL., belonging to the family Cucurbitaceae, is a genus containing 17 creeping herbaceous species mainly distributed in East Asia. It can be divided into two subgenera based on different fruit morphology. Herein, we report eight complete chloroplast genome sequences of the genus Gynostemma, which were obtained by Illumina paired-end sequencing, assembly, and annotation. The length of the eight complete cp genomes ranged from 157,576 bp (G. pentaphyllum) to 158,273 bp (G. laxiflorum). Each encoded 133 genes, including 87 protein-coding genes, 37 tRNA genes, eight rRNA genes, and one pseudogene. The four types of repeated sequences had been discovered and indicated that the repeated structure for species in the Subgen. Triostellum was greater than that for species in the Subgen. Gynostemma. The percentage of variation of the eight cp genomes in different regions were calculated, which demonstrated that the coding and inverted repeats regions were highly conserved. Phylogenetic analysis based on Bayesian inference and maximum likelihood methods strongly supported the phylogenetic position of the genus Gynostemma as a member of family Cucurbitaceae. The phylogenetic relationships among the eight species were clearly resolved using the complete cp genome sequences in this study. It will also provide potential molecular markers and candidate DNA barcodes for future studies and enrich the valuable complete cp genome resources of Cucurbitaceae.